The Usage and Efficiency of RFID among Road Users in Johor Bahru - Loh, Xiao Tong; Muhammad Ammar Shafi; Yusoff, Mohd Zarir (Research in Management of Technology and Business, 2023)
Due to the population of Malaysia rise every year and the demand of motor vehicle in the road increase, so the road users in Malaysia growth rapidly. The demand of toll payment system also increase accordingly. High usage of toll payment directly affects to the longer time in passing the toll and bring the delay of issues. One of the factors of delay issues is the toll detection problem at the toll payment booth. Many type of toll payment system implementation at the toll payment booth but Radio Frequency Identification (RFID) seem more prominent. Even through RFID is entrenched in the market but there are still challenges in implementation of the technology. Therefore, this study seeks to identify the usage and efficiency of RFID among road users. The research methodology adopted in this research is quantitative methods and the instrument that use to collect the data is questionnaires. The location of this research was conducted at Johor Bahru and the respondents of this research are driver with driver’s license. The results of this study show that RFID has the potential in providing convenient toll tracking to reduce the time wastage of passing the toll booth. The biggest challenge of RFID implementation are the financial and installation support due to the technical and cost of the technology. In conclusion, the research provides substantial knowledge of effective toll management with RFID implementation in automatic toll payment system at the roll collection sector